2002
DOI: 10.1007/s00213-001-0952-7
|View full text |Cite
|
Sign up to set email alerts
|

The GABA B antagonist CGP56433A attenuates the effect of baclofen on cocaine but not heroin self-administration in the rat

Abstract: The specific GABA(B) antagonist CGP56433A attenuated the effect of baclofen on cocaine self-administration, suggesting that GABA(B) receptors are critical in mediating the anti-cocaine effect of baclofen. In combination with other studies, the data demonstrate that the susceptibility of baclofen and other GABA(B) agonists to receptor blockade depends on the behavioral response being studied. Whether this indicates different receptor mechanisms are involved (e.g., pre- versus post-synaptic effects or differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 29 publications
1
16
2
Order By: Relevance
“…The present finding that baclofen decreased the reinforcing properties of cocaine confirms previous reports that baclofen decreased cocaine selfadministration and responding for cocaine under a progressive ratio schedule of reinforcement (Brebner et al, 1999;Roberts and Andrews, 1997;Roberts et al, 1996;Shoaib et al, 1998). But by contrast to previous findings (Brebner et al, 2002;Stein, 1999, 2000), the reinforcing properties of heroin were not changed by baclofen. The lack of effect of baclofen in the present study may be related to the dose of heroin used, since it has been demonstrated that baclofen is effective in decreasing the self-administration of low doses of cocaine, but was ineffective in reducing responding for doses of cocaine higher than that used in the present study (Brebner et al, 2000a, b;Roberts et al, 1996).…”
Section: Differential Effects Of Baclofen On Cocaine and Heroin Reinfcontrasting
confidence: 92%
See 2 more Smart Citations
“…The present finding that baclofen decreased the reinforcing properties of cocaine confirms previous reports that baclofen decreased cocaine selfadministration and responding for cocaine under a progressive ratio schedule of reinforcement (Brebner et al, 1999;Roberts and Andrews, 1997;Roberts et al, 1996;Shoaib et al, 1998). But by contrast to previous findings (Brebner et al, 2002;Stein, 1999, 2000), the reinforcing properties of heroin were not changed by baclofen. The lack of effect of baclofen in the present study may be related to the dose of heroin used, since it has been demonstrated that baclofen is effective in decreasing the self-administration of low doses of cocaine, but was ineffective in reducing responding for doses of cocaine higher than that used in the present study (Brebner et al, 2000a, b;Roberts et al, 1996).…”
Section: Differential Effects Of Baclofen On Cocaine and Heroin Reinfcontrasting
confidence: 92%
“…The lack of effect of baclofen in the present study may be related to the dose of heroin used, since it has been demonstrated that baclofen is effective in decreasing the self-administration of low doses of cocaine, but was ineffective in reducing responding for doses of cocaine higher than that used in the present study (Brebner et al, 2000a, b;Roberts et al, 1996). In this regard, the dose of heroin used in the present study (0.12 mg/kg/ infusion) was high relative to the dose used in other studies (0.06 mg/kg/infusion Stein, 1999, 2000); 0.025 mg/kg/ infusion (Brebner et al, 2002)). However, it is interesting to note that baclofen may have differential effects on cocaine and heroin self-administration, as the GABA B receptor antagonist CGP56433A reversed baclofen-induced decreases in cocaine, but not heroin, self-administration, suggesting a direct role for GABA B receptors in cocaine reinforcement only (Brebner et al, 2002).…”
Section: Differential Effects Of Baclofen On Cocaine and Heroin Reinfcontrasting
confidence: 53%
See 1 more Smart Citation
“…In these studies, we investigated the behavioral effects of mice lacking GABA B(1) receptor subunit in animal models of anxiety and depression and provide evidence for a role of GABA B receptors in the modulation of anxiety-and depression-like behavior. To further substantiate these observations in anxiety and depression paradigms, we investigated the behavioral effects of acute and chronic treatment of the selective GABA B receptor positive modulator GS39783 and the previously identified GABA B receptor antagonist CGP56433A (Brebner et al, 2002;Froestl et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, GABA B receptor activation via baclofen or other agonists attenuates many of the neurochemical and behavioral effects elicited by drugs of abuse. Baclofen administration reduces self-administration of d-amphetmaine (Brebner et al, 2005), nicotine (Fattore et al, 2002;Paterson et al, 2004a, b), heroin (Xi and Stein, 1999;Di Ciano and Everitt, 2003) alcohol (Colombo et al, 2002), and cocaine (Roberts et al, 1996;Brebner et al, 2000Brebner et al, , 2002b.…”
Section: Introductionmentioning
confidence: 99%